Aortic Thrombosis following COVID-19: A Systematic Review - Petrov, Asen; De Glee Romera, Juan Pablo; Wilbring, Manuel; Alexiou, Konstantin; Kappert, Utz; Matschke, Klaus Ehrhard; Tugtekin, Sems-Malte (The Thoracic and Cardiovascular Surgeon, 2022)
Background Arterial and venous thromboses associated with the coronavirus disease 2019 (COVID-19) have been well described. These events are caused by a hypercoagulable state due to endotheliopathy and infection-driven coagulopathy. There has been an ever-increasing number of documented cases of aortic thrombosis (AoT) in COVID-19 patients. We conducted a systematic review of current scientific literature to identify and consolidate evidence of AoT in COVID-19 patients.Methods A systematic review of literature was conducted between March 15, 2020, and May 1, 2021, on PubMed and Cochrane databases. Additionally, a case from our facility was included.Results A total of 38 studies (12 case series and 26 case reports) and a case from our facility describing AoT in 56 COVID-19 patients were included. Patients were aged 64.8 ± 10.5 years, were predominantly male (75%), and had several comorbidities. AoT was symptomatic in 82,14% of patients; however, when D dimers were reported, they were significantly elevated even in otherwise asymptomatic patients. Most patients had no previous history of aortic disease. Thrombosis was described in all parts of the aorta, with several cases reporting multiple locations. The median reported time until development of AoT was 10 days. Peripheral thrombosis occurred in 73.21% of cases, most commonly causing lower limb ischemia. Mortality rate was 30.4%.Conclusions AoT can occur with no clinical symptoms or as a primary symptom in otherwise asymptomatic COVID-19 patients. D dimers are a highly sensitive diagnostic tool. Diagnosis of this condition prior to development of complications could be instrumental in saving many lives.
Keywords: aorta/aortic; blood; coagulation/anticoagulation; cardiac; infection; ischemia/reperfusion; stroke